Origin, Methods, and Evolution of the Three Nurses’ Health Studies - Bao, Ying; Bertoia, Monica L.; Lenart, Elizabeth B.; Stampfer, Meir J.; Willett, Walter C.; Speizer, Frank E.; Chavarro, Jorge E. (American journal of public health (1971), 2016)
We have summarized the evolution of the Nurses’ Health Study (NHS), a prospective cohort study of 121 700 married registered nurses launched in 1976; NHS II, which began in 1989 and enrolled 116 430 nurses; and NHS3, which began in 2010 and has ongoing enrollment. Over 40 years, these studies have generated long-term, multidimensional data, including lifestyle- and health-related information across the life course and an extensive repository of various biological specimens. We have described the questionnaire data collection, disease follow-up methods, biorepository resources, and data management and statistical procedures. Through integrative analyses, these studies have sustained a high level of scientific productivity and substantially influenced public health recommendations. We have highlighted recent interdisciplinary research projects and discussed future directions for collaboration and innovation.